(3GdWQb GdehVMI ddCSGfjO GdoeUMMI hgh KHJ ddeDdas - (3TeS GdOjf Hf YHO Gddg Hf aJM GdaQZdjs; (3ehSi GdYbGHj GddHfGfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa bOQ YdeGA gPg GdCeI GdeMeOjI hSdSd CSGfjOge hLYdgG oeJUdI Edi NjQ GdHQjI s
(3BNQgG (B:s
(3faYfG Gddg Hge hMTQfG aj ReQJge hGdMeO ddg QH GdYGdejf hgh MSHfG hfYe Gdhcjd s
(3HChd GdfSNI ELGRI ddeDda ef TjNI TeS GdOjf eMeO Hf SGde GdMfai GdTGaYi GdeJhaj SfI (B1181(3g` hHBNQgG bUjOI ef fXe GdeDda aj QKGA TjNg GdMfajs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B43s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B283 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQ (B((3oeUWdM GdMOjK (B840) s
Keywords: (3GdJGQjNs